If it's not what You are looking for type in the equation solver your own equation and let us solve it.
25y-35=5(5y-7)
We move all terms to the left:
25y-35-(5(5y-7))=0
We calculate terms in parentheses: -(5(5y-7)), so:We get rid of parentheses
5(5y-7)
We multiply parentheses
25y-35
Back to the equation:
-(25y-35)
25y-25y+35-35=0
We add all the numbers together, and all the variables
=0
y=0/1
y=0
| 12x-5=6-x | | x+95+x+63=196 | | 2x²-7x=5 | | 1/3(6x+24)-20=3x-18 | | 4x+2=6(x-8) | | 2-0.9h=2 | | 13h+7=-h | | 2(4×-3)=5x-27 | | 25x+37=5x-12 | | 5(m-20)=20 | | 12y+6=2(6y+3) | | x÷10=13 | | 8=3(3x-6 | | x/3+6=-15.3 | | -369=6(-11x+4)+3 | | 5x-8=-6x | | 0.5x-3=3.9x-20 | | -7+1/6x=5 | | 2.6=p/2 | | 7k-7(1-5k)=40-5k | | -8(5x-8)=264 | | j+3=−14 | | 6(2x+9)-(11x-4)=7 | | 3(500-a)+10a=3600 | | -3k-22-8k=11 | | 5.72x+19.34-2.42x=3.5x+12 | | 8a+10=90 | | 5a-(2a+3)=2(a-3) | | 12+2=-2(9x-7) | | 30x=20x+50 | | 24x-6(3x-5)=11(4×+1) | | 61=5d-4 |